Legal regulation of creating and sros financial services market - Ящищак, Оксана Романівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The thesis analyzed (in particular on the basis of comparative analysis of legislation of Ukraine and the laws of some foreign countries) system and the powers of state bodies in regulations of financial institutions, prompted by reallocating powers of financial regulators. Investigate the legal status of self-regulatory organizations in the financial services market.